Empowering African Researchers: Building Data and Coding Skills with The Carpentries - Trusler, Angelique (My University, 2024)
Empowering African Researchers: Building Data and Coding Skills with The Carpentries - AfricArXiv Open Science Webinar Series 2024
This webinar session focused on helping African researchers start their data and coding skills journey. They learned the following: Fundamental coding techniques to streamline their research workflow Effective data management strategies to organize and analyze their data and Practical tips on using open-source tools to enhance their research capabilities The discussions had during the session will help anyone looking to learn foundational coding and data science skills.
Keywords: Open Science; Open Access; Research; Africa; Data; Coding; African Research; AfricArXiv; The Carpentries; Skills